GLOBAL SOCIAL MOVEMENT : UPAYA MASYARAKAT INTERNASIONAL DALAM MERESPON TINDAK KEJAHATAN GENOSIDA MELALUI RESOLUSI KONFLIK NIR-KEKERASAN PADA KASUS ISRAEL – PALESTINA - Salsabila Nanda Fadya; M. Nabil Suhendra; Emil Pinata; Jurena Hasibuan; Vieronica Varbi Sununianti; Deni Aries Kurniawan (Jurnal Analisa Sosiologi, 2024)
This article examines the social manifestations of the Israeli-Palestinian conflict by highlighting the role of global social movements, such as Boycott, Divestment and Sanctions (BDS), as a response to human rights violations, genocidal crimes and longstanding conflict. The main focus of this research is to analyze the potential of nonviolent movements in building dialogue, easing tensions, and supporting the effectiveness of diplomatic negotiations to achieve peaceful resolutions. This research uses a literature review approach by utilizing books, journal articles, and media reports as primary sources. The results show that resource mobilization theory can explain the success of the boycott movement, which is supported by a structured organization, cross-country cooperation, and global solidarity networks. The movement had an impact on the formation of public opinion, changes in international policy, and the development of diplomacy. However, to increase its effectiveness, broader support, solid international cooperation, and concrete diplomatic steps from the global community, including Indonesia's active role, are needed to realize justice and sustainable peace.